Integrating Environmental Sustainability Considerations into Food and Nutrition Policies: Insights from Australia’s National Food Plan - Ridgway, Ella Megan; Lawrence, Mark Andrew; Woods, Julie (Frontiers in Nutrition, 2015)
The environmental sustainability (ES) of food systems is a critical challenge for policy-makers. This is a highly contested policy area with differing views among stakeholders. The aim of the study was to develop a better understanding of how ES considerations are addressed in Australian food and nutrition policies and the way that consultation processes affect final policy outcomes. A mixed-methods study design combined a detailed chronology of key policy developments (2009 – 2015), a content analysis of written submissions obtained during the NFP’s consultation period (2011 – 2013) and a framing analysis of the sustainability perspectives - efficiency, demand restraint and system transformation – in the NFP’s Issues, Green and White Papers. There were 555 written submissions responding to two consultation papers. Stakeholders represented all sectors of Australia’s food system including government, non-government organizations, the food supply chain, research and academic institutions and members of the general public. Around 74% of submissions referred to ES considerations and approximately 65% supported their inclusion into the final policy. Efficiency frames were most dominant; emphasizing a production-oriented approach that regards the environment as a natural resource base for food production but overlooks consumption and equity concerns. Despite strong support for the inclusion of ES considerations in the NFP the influence of Australia’s sociopolitical context, powerful, industry-dominated stakeholders and a reliance on traditional production-oriented perspectives delivered a business-as-usual approach to food policy-making. It has since been replaced by an agricultural strategy that provides only cursory attention to ES. Our findings indicate that Australia’s political environment is not sufficiently mature for ES considerations to be integrated into food and nutrition policies. We propose reforms to the current consultation process in Australia to better support this integration by promoting greater transparency and participation in the development of food and nutrition policy-making.